A quantitative map of human Condensins provides new insights into mitotic chromosome architecture - Ellenberg Jan (University of Dundee, 2019)
FRAP experiments of Condensin-mEGFP subunits on the metaphase plate.
Keywords: Chromosomes; Human chromosomes